CRISPR adaptation in Escherichia coli subtypeI-E system. (20th November 2013) - Kiro, Ruth; Goren, Moran G.; Yosef, Ido; Qimron, Udi
Abstract : The CRISPRs (clustered regularly interspaced short palindromic repeats) and their associated Cas (CRISPR-associated) proteins are a prokaryotic adaptive defence system against foreign nucleic acids. The CRISPR array comprises short repeats flanking short segments, called 'spacers', which are derived from foreign nucleic acids. The process of spacer insertion into the CRISPR array is termed 'adaptation'. Adaptation allows the system to rapidly evolve against emerging threats. In the present article, we review the most recent studies on the adaptation process, and focus primarily on the subtype I-E CRISPR–Cas system of Escherichia coli .